Pengaruh Motivasi Kerja Kepemimpinan dan Beban Kerja terhadap Kinerja Pegawai Kantor Camat Batang Angkola Kabupaten Tapanuli Selatan - Lanniari Hasibuan; Roni Artha Lumbantobing; Gusti Oloan Siregar; Gusni Armi Pasaribu (Manajemen dan Bisnis, 2022)
Problem  this study is how influence job motivation on employee’s performance. How influence  leadership  on employee’s performance. How influence  work load  on employee’s performance. How influence job motivation, leadership     and work load  on employee’s performance. The purpose  this study to determine and analyze the effect job motivation on employee’s performance. Determine and analyze the effect  leadership on employee’s performance. Determine and analyze the effect work load on employee’s performance. Determine and analyze the effect job motivation, leadership and work load  on employee’s performance. Sample in the study is 34  employee’s. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results  the study indicate  job motivation variable has a positive and significant effect on employee’s performance.  Leadership     variable has a positive and significant effect on employee’s performance. Work load  variable has a positive and significant effect on employee’s performance.  Job motivation, leadership and work load  variable has a positive and significant effect on employee’s performance.